Analgesic benefits and clinical role of the posterior suprascapular nerve block in shoulder surgery: a systematic review, meta‐analysis and trial sequential analysis. (3rd October 2019) - Cho, N.; Kang, R. S.; McCartney, C. J. L.; Pawa, A.; Costache, I.; Rose, P.; Abdallah, F. W.
Summary: The posterior suprascapular nerve block has been proposed as an analgesic alternative for shoulder surgery based on the publication of several comparisons with interscalene block that failed to detect differences in analgesic outcomes. However, quantification of the absolute treatment effect of suprascapular nerve block on its own, in comparison with no block (control), to corroborate the aforementioned conclusions has been lacking. This study examines the absolute analgesic efficacy of suprascapular nerve block compared with control for shoulder surgery. We systematically sought electronic databases for studies comparing suprascapular nerve block with control. The primary outcomes included postoperative 24‐h cumulative oral morphine consumption and the difference in area under the curve for 24‐h pooled pain scores. Secondary outcomes included the incidence of opioid‐related side‐effects (postoperative nausea and vomiting) and patient satisfaction. Data were pooled using random‐effects modelling. Ten studies (700 patients) were analysed; all studies examined landmark‐guided posterior suprascapular nerve block performed in the suprascapular fossa. Suprascapular nerve block was statistically but not clinically superior to control for postoperative 24‐h cumulative oral morphine consumption, with a weighted mean difference (99%CI) of 11.41 mg (−21.28 to −1.54; p = 0.003). Suprascapular nerve block was also statistically but not clinically superior to control for area under the curve of pain scores, with a mean difference of 1.01 cm.h. Nonetheless, suprascapular nerve block reduced the odds of postoperative nausea and vomiting and improved patient satisfaction. This review suggests that the landmark‐guided posterior suprascapular nerve block does not provide clinically important analgesic benefits for shoulder surgery. Investigation of other interscalene block alternatives is warranted.